Is short term intraoperative application of disinfectants harmful to breast implants in breast reconstruction? An experimental study and literature survey - Schmitz, Marweh; Schubert, Dirk W.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian; Horch, Raymund E. (Journal of the Mechanical Behavior of Biomedical Materials, 2019)
Objectives: Bacterial contamination of breast implants and biofilm formation has been discussed as a major reason for implant loss and capsular contraction. Intra- and perioperative treatment of breast implants with disinfectants to prevent bacterial contamination has been frequently reported. Given the increasing awareness of concerns about product liability the question of whether short-time irrigation of implants with antimicrobial substances during the operative procedure would potentially alter the integrity of the implant shell has attracted legal and medical interest. In this study we therefore investigated whether irrigating breast implants with antimicrobials commonly used in clinical practice with a clinically relevant application time would affect the physical integrity of the implant shell.
CRIS-Team WoS Importer:2019-02-21